The DLSU-Manila website, www.dlsu.edu.ph, received the People's Choice Award - De La Salle University, Manila (Animo Repository, 2003)
The DLSU-Manila website, www.dlsu.edu.ph, received the People's Choice Award in the Schools Category at the 6th Philippine Web Awards (PWA). People's Choice Award was given to the web site, which garnered the most number of votes via SMS or online in its category. The Schools Category was a new classification, which used to be part of Education and Resources.